PENGARUH MEDIA PEMBELAJARAN DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA - Haryanti Haryanti (Universitas Indraprasta PGRI, 2019)
The study aims to determine: 1) The effect of instructional media and vocabulary mastery towards English speaking ability. 2) The effect of Vocabulary mastery towards English speaking ability. 3) The effect of instructional media on English speaking ability. The affordable population is class X of Uswatun Hasanah Private Vocational School, Mardi Bhakti Private Vocational School, East Jakarta. The sample of this research is 70 respondents in this study. The method used is an experiment. Inference analyses used are ANOVA two-way factorial 2x2. The results of this study show:1) There is no significant effect on instructional media and vocabulary mastery towards English speaking ability. This result is evidenced by the acquisition of sig.0,258 > 0,05 and F observe 1,305. 2) There is a significant effect on vocabulary mastery towards English speaking ability. This result is evidenced by the acquisition of sig.0,0,012< 0,05 and F observe 6,741. 3) There is a significant effect on instructional media towards English speaking ability. This result is evidenced by the acquisition of sig.0,000 < 0,05 and F observe 85,435.Key Words: instructional media; game; vocabulary mastery; speaking skill